2016
DOI: 10.1016/j.ncrna.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in cancer diagnosis and therapy

Abstract: Cancer invasion involves a series of fundamental heterogeneous steps, with each step being distinct in its type regarding its dependence on various oncogenic pathways. Over the past few years, researchers have been focusing on targeted therapies to treat malignancies relying not only on a single oncogenic pathway, but on multiple pathways. Scientists have recently identified potential targets in the human genome considered earlier as non-functional but the discovery of their potential role in gene regulation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 51 publications
1
32
0
2
Order By: Relevance
“…Os ncRNAs são elementos regulatórios abundantes em humanos, mas ainda poucos explorados como potenciais candidatos a terapias gênicas [Rasool et al 2016]. Dentre os ncRNAs, os miRNAs são os mais estudados e osúnicos que possuem uma ferramenta para análise integrada com redes e métricas de redes complexas [Nair et al 2014].…”
Section: Trabalhos Relacionadosunclassified
“…Os ncRNAs são elementos regulatórios abundantes em humanos, mas ainda poucos explorados como potenciais candidatos a terapias gênicas [Rasool et al 2016]. Dentre os ncRNAs, os miRNAs são os mais estudados e osúnicos que possuem uma ferramenta para análise integrada com redes e métricas de redes complexas [Nair et al 2014].…”
Section: Trabalhos Relacionadosunclassified
“…In grade 3 breast cancer, lncRNA-BC4 expression was significantly lower and lncRNA-BC5 expression was significantly higher. lncRNAs have been demonstrated to be easily detected in bodily fluids by multiple studies, such as lncRNA RP11-445H22.4 was found to be significantly increased in breast cancer patients serum with high sensitivity and specificity [118]. Zhao et al identified a set of lncRNAs are deregulated in breast cancer patients and distinguish low-risk patients from high risk patients.…”
Section: Breast Cancermentioning
confidence: 99%
“…ncRNAs are also suggested to play an important role in several physiological conditions, including nearly all types of cancer [138,139,140]. The long non-coding RNA (lncRNA) H19 has been identified to be markedly overexpressed in pancreatic tumor tissues and cell lines, with a positive correlation with the invasive and migratory potential of the tumors [114,141,142].…”
Section: Molecular Alterations Driving Pancreatic Cancer Progressionmentioning
confidence: 99%